2020
DOI: 10.1016/j.adaj.2019.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Asthma, chronic obstructive pulmonary disease, tooth loss, and edentulism among adults in the United States

Abstract: Background.-Adults with chronic respiratory conditions, specifically asthma and/or chronic obstructive pulmonary disease (COPD) may be at risk for poor oral health due to systemic inflammation, challenges in routine dental care, and side effects of medications used to treat these conditions. We examined the association of asthma, COPD, and co-existing asthma and COPD (asthma-COPD overlap syndrome, or ACOS) with tooth loss among US adults.Methods.-Cross-sectional design was employed using 2016 Behavioral Risk F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…As the major cause of tooth loss, periodontal disease was associated with several systemic diseases under the inflammatory mechanism (Kim and Amar, 2006;Linden et al, 2013;Genco and Sanz, 2020). Tooth loss has been associated with chronic diseases and conditions, such as diabetes (Kapp et al, 2007;Winning et al, 2017), cardiovascular disease (Okoro et al, 2005;Winning et al, 2020), stroke (Joshipura et al, 2003), cancer (Maisonneuve et al, 2017;Michaud et al, 2017), obesity (Österberg et al, 2010), depression (Okoro et al, 2012), memory impairment (Okamoto et al, 2015), arthritis (de Pablo et al, 2008), and respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD) (Wang et al, 2009;Thomas et al, 2010;Bansal et al, 2013;Dwibedi et al, 2020). However, most of these studies have focused on an isolated chronic disease without controlling for other concurrent chronic diseases or multimorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…As the major cause of tooth loss, periodontal disease was associated with several systemic diseases under the inflammatory mechanism (Kim and Amar, 2006;Linden et al, 2013;Genco and Sanz, 2020). Tooth loss has been associated with chronic diseases and conditions, such as diabetes (Kapp et al, 2007;Winning et al, 2017), cardiovascular disease (Okoro et al, 2005;Winning et al, 2020), stroke (Joshipura et al, 2003), cancer (Maisonneuve et al, 2017;Michaud et al, 2017), obesity (Österberg et al, 2010), depression (Okoro et al, 2012), memory impairment (Okamoto et al, 2015), arthritis (de Pablo et al, 2008), and respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD) (Wang et al, 2009;Thomas et al, 2010;Bansal et al, 2013;Dwibedi et al, 2020). However, most of these studies have focused on an isolated chronic disease without controlling for other concurrent chronic diseases or multimorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, metabolic diseases can increase susceptibility to dental caries and missing teeth due to dysregulated inflammation and immune functions. In patients with missing teeth, systemic inflammation and immune dysfunctions can also increase susceptibility to cancer, respiratory diseases, such as asthma and chronic obstructive pulmonary disease, and digestive diseases, such as liver diseases (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a population-based study revealed that persons diagnosed with asthma were significantly less likely to receive dental care than the general population. 19 This study attempted to address this phenomenon by analyzing reported cases of newly diagnosed asthma within 2 years of the NHANES survey, when data were collected regarding the dental filling status of persons. As a result, it is assumed that more long-term trends in differential dental care among persons diagnosed with asthma versus the general population would be minimized.…”
Section: Discussionmentioning
confidence: 99%